2019
DOI: 10.3390/ijerph16244983
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term PTSD Risks in Emergency Medical Technicians Who Responded to the 2016 Taiwan Earthquake: A Six-Month Observational Follow-Up Study

Abstract: Although several factors associated with posttraumatic stress disorder (PTSD) in disaster rescue workers were identified in previous studies, the results were inconsistent. This study aimed to explore the prognostic factors of PTSD among disaster rescuers using different screening tools. A 6.4 magnitude earthquake struck southern Taiwan on February 6, 2016. Emergency medical technicians (EMTs) who responded to the earthquake were recruited. The initial survey was conducted one month after the earthquake using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Furthermore, front-line medical staff is more likely to encounter patients dying from COVID-19. Research showed that the disposal of corpses results in negative psychological reactions and a poor QoL, which was the case in a sample of earthquake rescuers ( Hsiao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, front-line medical staff is more likely to encounter patients dying from COVID-19. Research showed that the disposal of corpses results in negative psychological reactions and a poor QoL, which was the case in a sample of earthquake rescuers ( Hsiao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…In China, PTSD studies involving survivors of natural disasters have focused mainly on hospitalization, particularly those examining the 2008 Wenchuan earthquake. However, few studies have explored long-term outcomes, such as 1-2 year or several years after disasters, for survivors who are at high risk of PTSD [14,15]. Therefore, prospective follow-up of injured survivors is required to identify risk factors for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies included in the review investigated the long-term psychological impacts among EMS providers (7,(10)(11)(12). Only one study was conducted regarding the response to a large-scale emergency-the COVID-19 pandemic (1).…”
Section: Discussionmentioning
confidence: 99%